Half-and-half nails in a pediatric patient after chemotherapy. (2nd October 2015) - Afsar, Fatma Sule; Ozek, Gulcihan; Vergin, Canan
Abstract: Half-and-half nail, characterized by a reddish brown distal band with a sharply demarcated white proximal band, is a specific manifestation of chronic kidney disease, but it is unusual to occur after chemotherapy. We report a seven-year-old girl who developed half-and-half nails in her fingers one month after treatment with modified Berlin-Frankfurt-Munster protocol followed by maintenance therapy with oral methotrexate and 6-mercaptopurine for pre-B acute lymphoblastic leukemia.